Pre-tertiary blueschist facies metamorphism in the Hellenides evidenced by detrital blue amphiboles in the Paleocene flysch of the Othrys mountain - PETRAKAKIS, K.; FAUPl, P.; MIGIROS, G.; PAVLOPOULOS, A. (Bulletin of the Geological Society of Greece, 2001)
Analyses of detrital blue amphiboles from Paleocene flysch deposits of the western Othrys Mountain show a narrow compositional variability and are comparable with published analyses from the Cycladic Islands. In contrast, analyses from Pelagonian blueschists (Olympos, Ossa, Ambelakia) show a wide compositional variation that is rather due to the lithological variability of their parental rocks and incomplete overprinting by blueschist facies metamorphism. Combined with published evidence, the above features exclude the Pelagonian rocks from being the potential source of the detrital blue amphiboles. The latter were derived from a source with "Cycladic" affinities that (1) presently is not exposed, but may have been covered tectonically during the Tertiary and (2) has been already exposed to erosion in response to subduction at the Pindos oceanic realm at the active external Pelagonian margin during Maastrichtian/Paleocene times. The data demonstrate that blueschist facies metamorphism in the Hellenides started at Pre-Tertiary times.